Psychoemotional Burnout of Personality: Theoretical Aspects of the Problem - Rudnytskyi, Oleksandr (Psychological Prospects Journal, 2024)
Purpose. The objective is to conduct an analytical review of multidirectional studies on psychoemotional burnout of personality as a phenomenon that negatively impacts and significantly complicates its professional activity and interpersonal communication.Methods. To achieve this objective, the following scientific-theoretical methods were applied: analysis, synthesis, generalization, which allowed for the revelation of substantive and functional parameters of psychoemotional burnout.Results. A range of studies explains the cause-and-effect essence of psychoemotional burnout by the specifics of a person's professional activity. Burnout leads to the appearance of psychological and/or psychosomatic changes, adversely affects affective balance, generates increased stress, heightened anxiety, oppressive frustration, and other depressive feelings, experiences, and behavioral modalities. Monotonous and emotionally exhausting as well as physically amortizing professional activity in a specific field, along with permanent pressure from administration, may stimulate feelings of mental discomfort, increase the frequency of intra- and interpersonal conflicts, stimulate social withdrawal, loneliness, and experiences of disappointment in life values.Conclusions. Psychoemotional burnout is regarded as a complex and branching phenomenon that exerts an unfavorable influence on a person's life and complicates their communicative relationships within the family and at work. Manifestations of psychoemotional burnout and psychophysical exhaustion have been studied extensively with diverse samples (students, police officers, medical professionals, firefighters, athletes, deprived children, etc.). A common feature of the analyzed studies is the recognition of the uncomfortable and destructive pressure of psychoemotional burnout on the affective-cognitive behavioral tactics and strategies of the individual.